2015
DOI: 10.1088/0964-1726/24/8/085017
|View full text |Cite
|
Sign up to set email alerts
|

Damage analysis of CFRP-confined circular concrete-filled steel tubular columns by acoustic emission techniques

Abstract: Damage properties of carbon fiber-reinforced polymer (CFRP) confined circular concrete-filled steel tubular (CCFT) columns were analyzed through acoustic emission (AE) signals. AE characteristic parameters were obtained through axial compression tests. The severity of damage to CFRP-CCFT columns was estimated using the growing trend of AE accumulated energy as basis. The bearing capacity of CFRP-CCFT columns and AE accumulated energy improved as CFRP layers increased. The damage process was studied using a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The AE methods were also used for safety monitoring of the civil structures and thermal fracture of the glass materials (Kim and Sache, 1986; Li et al, 2015; Sagar and Prasad, 2012). One of the major challenges of the fatigue crack–related AE signals is that a simple fatigue experiment could generate a huge amount of AE data which could make it difficult to analyze the individual AE waveform.…”
Section: Introductionmentioning
confidence: 99%
“…The AE methods were also used for safety monitoring of the civil structures and thermal fracture of the glass materials (Kim and Sache, 1986; Li et al, 2015; Sagar and Prasad, 2012). One of the major challenges of the fatigue crack–related AE signals is that a simple fatigue experiment could generate a huge amount of AE data which could make it difficult to analyze the individual AE waveform.…”
Section: Introductionmentioning
confidence: 99%
“…These studies proposed formulas based on the recorded AE to predict the damage level for the examined RC elements. Moreover, AE signals were used to analyze the damage of confined circular concrete-filled steel tubular (CCFT) columns [ 20 ] and FRP-CCFT columns and showed the possibility of AE to predict initial steel yielding and to provide failure warning [ 21 ]. The AE technique was also implemented for RC beams and revealed that AE parameters increased with increasing beam thickness [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emissions (AEs) refer to the effect generated when a material is subjected to an external load and the strain energy stored inside can be quickly released to generate an elastic wave, at which point an acoustic sound occurs. AE technology is a commonly used nondestructive testing and real‐time monitoring technology . It has been used for damage detection and evaluation of brittle materials.…”
Section: Introductionmentioning
confidence: 99%
“…AE technology is a commonly used nondestructive testing and real-time monitoring technology. 17 It has been used for damage detection and evaluation of brittle materials. AE signal analysis can help detect and monitor microcracks and their growth during the entire fracturing process of brittle materials.…”
Section: Introductionmentioning
confidence: 99%